2017
DOI: 10.1080/01930826.2017.1326264
|View full text |Cite
|
Sign up to set email alerts
|

Creating a Virtuous Circle of Student Engagement with the Tech Corner

Abstract: While many academic libraries have followed the public library lead in developing makerspaces, not all libraries have the money or space to dedicate to such large-scale operations. This case study explores a different approach to engaging users with new technology and investigates how to support their creativity without a costly investment in space and staffing. It demonstrates not only how students can be provided a virtual space to explore technology equipment, but also how their opinions can be leveraged fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Instead, the current digital equity gap is characterized by what sort of technology students have access to, where they access it, and what kind of infrastructure is in place to enable its use. Before COVID-19, for example, libraries provided a mechanism for students to access technology they would otherwise be unable to use (Schuck et al, 2017). Such resources are necessary, as recent survey of 1,043 families in Watts, South Los Angeles and Boyle Heights, CA has shown that close to 50% of students rely on school-issued equipment to do their homework, 20% do not have a device at all, and 16% do not have any access to the internet (Partnership for LA Schools, 2020).…”
Section: Understanding the Digital Equity Gap K-12 Digital Equity Gapmentioning
confidence: 99%
“…Instead, the current digital equity gap is characterized by what sort of technology students have access to, where they access it, and what kind of infrastructure is in place to enable its use. Before COVID-19, for example, libraries provided a mechanism for students to access technology they would otherwise be unable to use (Schuck et al, 2017). Such resources are necessary, as recent survey of 1,043 families in Watts, South Los Angeles and Boyle Heights, CA has shown that close to 50% of students rely on school-issued equipment to do their homework, 20% do not have a device at all, and 16% do not have any access to the internet (Partnership for LA Schools, 2020).…”
Section: Understanding the Digital Equity Gap K-12 Digital Equity Gapmentioning
confidence: 99%
“…Another study endorsed the idea of constructing creative spaces in learning environments such as libraries, as they support the philosophy of collaboration, discovery, and integration of library services [75]. Creating makerspaces in libraries to support students' creative abilities was also endorsed by Schuck et al [70]. Makerspaces in libraries are also considered to be innovative for business education and entrepreneurship and are often combined with other features encouraging creativity [77].…”
Section: Learning Environmentsmentioning
confidence: 99%
“…A full description of the OBS is available on the One Button Studio website (https://onebutton.psu.edu). The OBS was identified by Schuck, Wainscott, Church-Duran, and Del Bosque (2017) as a solution to fulfill recommendations from a faculty technology advisory committee, which had identified a lack of faculty video production support on their campus. The OBS was also employed by Girven (2016) to support faculty and students in a university library.…”
Section: Challenges To Implementationmentioning
confidence: 99%